The Effects of High Fat Diet and Resveratrol on Mitochondrial Activity of Brown Adipocytes - Cheol Ryong Ku; Yoon Hee Cho; Zhen-Yu Hong; Ha Lee; Sue Ji Lee; Seung-soo Hong; Eun Jig Lee (Endocrinology and Metabolism, 2016)
BackgroundResveratrol (RSV) is a polyphenolic phytoalexin that has many effects on metabolic diseases such as diabetes and obesity. Given the importance of brown adipose tissue (BAT) for energy expenditure, we investigated the effects of RSV on brown adipocytes.MethodsFor the in vitro study, interscapular BAT was isolated from 7-week-old male Sprague Dawley rats. For the in vivo study, 7-week-old male Otsuka Long Evans Tokushima Fatty (OLETF) rats were divided into four groups and treated for 27 weeks with: standard diet (SD); SD+RSV (10 mg/kg body weight, daily); high fat diet (HFD); HFD+RSV. RSV was provided via oral gavage once daily during the in vivo experiments.ResultsRSV treatment of primary cultured brown preadipocytes promoted mitochondrial activity, along with over-expression of estrogen receptor α (ER-α). In OLETF rats, both HFD and RSV treatment increased the weight of BAT and the differentiation of BAT. However, only RSV increased the mitochondrial activity and ER-α expression of BAT in the HFD-fed group. Finally, RSV improved the insulin sensitivity of OLETF rats by increasing the mitochondrial activity of BAT, despite having no effects on white adipocytes and muscles in either diet group.ConclusionRSV could improve insulin resistance, which might be associated with mitochondrial activity of brown adipocyte. Further studies evaluating the activity of RSV for both the differentiation and mitochondrial activity of BAT could be helpful in investigating the effects of RSV on metabolic parameters.